1996
DOI: 10.4141/cjas96-043
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age at photostimulation on reproductive efficiency and carcass characteristics. 2. Egg-type hens

Abstract: Increasing day length is the primary cue for the timing of sexual maturation in poultry. Typically, Single Comb White Leghorn (SCWL) pullets are reared under conditions of short days (8L:16D) until 18 wk of age. In this study, the effects of varying the age at photostimulation from 16, 18 or 20 wk of age were studied in terms of carcass composition at photostimulation and at sexual maturity, as well as reproductive performance.A flock of 1600 SCWL pullets (Shaver 288 strain) were housed in floor pens in light-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2001
2001
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 2 publications
2
3
1
Order By: Relevance
“…Intriguingly, despite the small window of body weight between strains at AFE, Smoky Joe hens continued to lag behind in weight at the time of and 1-week post-PS, suggesting that PS had an influence on the body weight increase of these hens. This is similar to studies in both broiler breeder and turkey hens, which showed that while body weight differed at the various ages of photostimulation, overall, there was no impact on the body weight of these hens at maturation ( Robinson et al, 1996 ; Applegate and Lilburn, 1998 ). Therefore, photostimulation was shown to only influence the age of the maturation process, potentially allowing these hens to reach their optimal body weight threshold at an earlier age.…”
Section: Discussionsupporting
confidence: 88%
“…Intriguingly, despite the small window of body weight between strains at AFE, Smoky Joe hens continued to lag behind in weight at the time of and 1-week post-PS, suggesting that PS had an influence on the body weight increase of these hens. This is similar to studies in both broiler breeder and turkey hens, which showed that while body weight differed at the various ages of photostimulation, overall, there was no impact on the body weight of these hens at maturation ( Robinson et al, 1996 ; Applegate and Lilburn, 1998 ). Therefore, photostimulation was shown to only influence the age of the maturation process, potentially allowing these hens to reach their optimal body weight threshold at an earlier age.…”
Section: Discussionsupporting
confidence: 88%
“…It has been postulated that age at first oviposition is influenced by external stimuli in addition to the genetic constitution of the birds. The age at first ovulation is influenced by supplemental light (Eitan and Sollan, 1991;Robinson et al, 1996) or not (Lupicki 1994), in the present study maintaining birds at continuous light resulted in decrease in age at first ovipositon. Although the decrease was lower than those reported by Lupicki, (1994) the decrease was not significantly altered due to 2-bromo-αergocriptine treatments.…”
Section: Modulation Of Prl On Egg Production Parameterssupporting
confidence: 49%
“…Robinson et al (2001) reported that early age at first oviposition impairs egg production since greater allocation of energy is towards ovary in young age, which might have caused impairment in ovarian control (Robinson et al, 1993). Secondly, limited body reserves would have been depleted by the time of peak egg production as reported by Robinson et al (1996). The results observed in the experiment indicate that high total egg production was primarily a function of higher rates of lay through out the laying period of 72 weeks, rather than age at sexual maturity.…”
Section: Modulation Of Prl On Egg Production Parametersmentioning
confidence: 97%
“…2 FF = fast-feathering; SF = slow-feathering; CON = formulated as a standard commercial diet to meet breeder-recommended nutrient levels; HIGH = formulated to contain at least 8%, and not more than 15% more protein, including essential amino acids, than the CON diet; LYF = large yellow follicles on the ovary. growth, and organ development at SM (Yuan et al, 1994;Robinson et al, 1996b;Zuidhof et al, 2007). Delaying PS results in increased early egg size in broiler breeders (Joseph et al, 2002;Renema et al, 2007) and a reduction in the incidence of multiple ovulations in turkeys (Woodard et al, 1974).…”
Section: Reproductive Parametersmentioning
confidence: 97%